THE TRANSFER OF THE KARANOGAI PRISTAVSTVO FROM THE STAVROPOL GOVERNORATE TO THE TEREK OBLAST: REFORMING ADMINISTRATION IN THE TEREK AND KUBAN OBLASTS, 1883–1888 - Volhonskij, Mihail Alekseevic; Arlykapov, Ahmet Aminovic (History, Archeology and Ethnography of the Caucasus, 2025)
This study examines the causes, objectives, and consequences of the administrative reform implemented by the Caucasian administration in March 1888, which entailed the transfer of the Karanogai Pristavstvo (district) from the Stavropol Governorate to the Terek Oblast. Analysis of newly identified archival sources from the Russian State Historical Archive and the State Archive of the Stavropol Krai reveals that this specific administrative change was a component of a broader initiative to reorganize the administrations of the Kuban and Terek Oblasts. The primary objective of this larger reform was to preserve the Kuban and Terek Cossacks as a distinct military estate. Consequently, the reform planned to subject all social and ethnic groups within both regions to the control of the Cossack military administration. The integration of the Karanogai Pristavstvo into the Terek Oblast under this framework was necessitated by the close economic and land-use relationship between the Karanogais and the Terek Cossacks. The reform, devised by the Caucasian administration under Prince A. M. Dondukov-Korsakov, entirely disregarded the interests of the Karanogai people. Its implementation in March 1888 compelled the administrations of the Stavropol Governorate and Terek Oblast to address the division of “the total Mohammedan capital of nomads in Stavropol Governorate” into two parts. In 1889, the issue of apportioning pasturelands and delineating a precise administrative boundary between the Terek Oblast and Stavropol Governorate arose. The latter question remained unresolved until 1917. Overall, the reform proved unsuccessful. First, it exacerbated conflicts over pastures and watering places among the nomads of the Nogai Steppe – namely, the Karanogais, Edishkul and Yedisan Nogais, and Turkmens – who were divided between the two administrative units by the reform. Second, it exerted a profoundly negative influence on the socio-economic development of the Karanogai people.